SISTEM RANTAI PASOK KOPI ROBUSTA DI KABUPATEN KEPAHIANG PROVINSI BENGKULU - Muhamad Mustopa Romdhon; Nusril Nusril; Dedy Setiawan (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2021)
Kepahiang Regency is ones of largest producing robusta coffee on Bengkulu Province. Many business actors are involved in the activities of this product supply chain system, they are supposed to be lower income This research tried to explain in a detailed and systematic description so that the three activities in the robusta coffee supply chain system in Kepahiang Regency. Snow ball sampling method was used to determine actors sample in Supply Chain System of Robusta Coffee. Secondary data was production, land size, and productifity were collected from Central Bureau of Statistics, Regional Agriculture Office of Kepahiang Regency and coffee consumption was collected from International Coffee Organization. Primary data was product, price, quantity, delivery time, payment, and delivery services. Data analysis used Hayami et al model for value added, share margin for financial flow, flow diagram for information and product flows. The results showed that there are three patterns of robusta coffee supply chain in Kepahiang Regency, namely Pattern 1: Coffee farmers –Village collectors – Regency Collectors-Coffee Shop Palembang. Pattern 2: Coffee farmers –Village collectors – Regency collectors 1– Coffee company- Exporter. Pattern 3: Coffee farmers - Regency collectors 2 - Coffee company - Exporter. Generally, business activities in the supply chain in namely 1) categorization of the quality and quantity of large products in the supply chains 2, and 3, 2) Flow of price information is obtained from business actors downstream as price maker to actors upstream as price taker in the supply chain system, and 3) financial flow and the largest marketing margin in supply chains 2, 3 and 1 respectively,and 4) the payment system being carried out in three, namely cash, credit and payment. Value added is received by company was Rp12.151 per kgs since it was grading treatment for gaining better product quality. The development of processing industry of robusta coffee could increase added value of product and income of actors in Supply Chain System, then contribute to regional economy.